2007
DOI: 10.1158/0008-5472.can-07-1083
|View full text |Cite
|
Sign up to set email alerts
|

The let-7 MicroRNA Represses Cell Proliferation Pathways in Human Cells

Abstract: MicroRNAs play important roles in animal development, cell differentiation, and metabolism and have been implicated in human cancer. The let-7 microRNA controls the timing of cell cycle exit and terminal differentiation in Caenorhabditis elegans and is poorly expressed or deleted in human lung tumors. Here, we show that let-7 is highly expressed in normal lung tissue, and that inhibiting let-7 function leads to increased cell division in A549 lung cancer cells. Overexpression of let-7 in cancer cell lines alte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

48
922
5
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,164 publications
(995 citation statements)
references
References 49 publications
48
922
5
11
Order By: Relevance
“…In support of the significance of our findings, reduced expression of let-7 is correlated with poor prognosis, as lung cancer patients with the least let-7 expression had shorter time of survival after surgery (Takamizawa et al, 2004;Yanaihara et al, 2006). We and others subsequently showed that let-7 directly regulates multiple oncogenes, including RAS, MYC and HMGA2 (Johnson et al, 2005;Lee and Dutta, 2007;Mayr et al, 2007;Sampson et al, 2007), and promoters of cell-cycle progression, such as CDC25A, CDK6 and Cyclin D2 (Johnson et al, 2007). Moreover, administration of let-7 blocks the growth of cultured lung cancer cells (Johnson et al, 2007).…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…In support of the significance of our findings, reduced expression of let-7 is correlated with poor prognosis, as lung cancer patients with the least let-7 expression had shorter time of survival after surgery (Takamizawa et al, 2004;Yanaihara et al, 2006). We and others subsequently showed that let-7 directly regulates multiple oncogenes, including RAS, MYC and HMGA2 (Johnson et al, 2005;Lee and Dutta, 2007;Mayr et al, 2007;Sampson et al, 2007), and promoters of cell-cycle progression, such as CDC25A, CDK6 and Cyclin D2 (Johnson et al, 2007). Moreover, administration of let-7 blocks the growth of cultured lung cancer cells (Johnson et al, 2007).…”
Section: Introductionsupporting
confidence: 82%
“…We and others subsequently showed that let-7 directly regulates multiple oncogenes, including RAS, MYC and HMGA2 (Johnson et al, 2005;Lee and Dutta, 2007;Mayr et al, 2007;Sampson et al, 2007), and promoters of cell-cycle progression, such as CDC25A, CDK6 and Cyclin D2 (Johnson et al, 2007). Moreover, administration of let-7 blocks the growth of cultured lung cancer cells (Johnson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 These findings led to growing interest in Let-7 and its role in cancer development and control. [8][9][10] It has been recently found that polymorphisms may affect miRNA-mediated regulation of cell functions. They can be present in the 3 0 -UTR of a target mRNA and in the genes involved in miRNA genesis and maturation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, miRNAs are central players during development (e.g., neural or cardiac; Abernathy & Yoo, 2015; Porrello, 2013; Reinhart et al., 2000) or immunity (Zhu, Pan & Qian, 2013). They play an important role in all cellular processes, such as cell proliferation (Johnson et al., 2007; Navarro & Lieberman, 2010), differentiation (Navarro & Lieberman, 2010), and apoptosis (Ghodgaonkar et al., 2009). They have been largely studied in cancer, in which they are described to function as oncogenes or tumor suppressor genes and are grouped under the term “oncomiRs” (Bracken, Scott & Goodall, 2016; Hayes, Peruzzi & Lawler, 2014).…”
Section: Micrornasmentioning
confidence: 99%